Evaluation of the Implementation of the Independent Curriculum in Elementary Schools - Ida Farida; Effy Mulyasari (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The implementation of the Merdeka Curriculum in Indonesian primary schools remains understudied from multiperspective evaluation standpoints, particularly in non-pilot district schools. This study aims to evaluate the implementation of the Merdeka Curriculum at the fifth grade of elementary schools, through a qualitative descriptive single case study design. Data were collected via semi-structured interviews with teachers, the principal, three students, and one parent; one full-cycle classroom observation using a 16-indicator structured sheet; and documentary analysis of ten institutional documents including lesson modules, learning pathway documents (ATP), diagnostic assessment instruments, and student report cards. Results indicate that teachers have developed learning tools aligned with Capaian Pembelajaran (CP), implemented differentiated instruction and project-based learning (P5), and adopted descriptive, competency-based assessment. The principal provided systematic support through training, supervision, and community learning facilitation. Students demonstrated increased engagement, confidence, and creativity. However, three key challenges were identified: suboptimal utilization of diagnostic assessment data for instructional differentiation, limited teacher creativity under time pressure, and partially implemented critical thinking facilitation. This study concludes that effective Merdeka Curriculum implementation requires sustained teacher professional development, strong institutional leadership, and continuous multi-stakeholder collaboration.